Characterization of Gold Nanoparticles Synthesized with Zingiber zerumbet Extracts - Wayne C. Liao; Collin S. Liao; Yu-Chen Lin; Ching-Yi Lien (Journal of Chemistry)
Gold nanoparticles have been used as drug carriers and imaging reagents. The plant extract-capped gold nanoparticles provide better properties than chemically synthesized gold nanoparticles. In this study, Zingiber zerumbet extract-mediated green production of gold nanoparticles (Z. zerumbet@Au NPs) was established. Based on the UV-visible spectroscopy and transmission electron microscope (TEM) results, most Z. zerumbet@Au NPs were spherical. When more Z. zerumbet extracts were added, more spherical nanoparticles were formed. The hydrodynamic size changed slightly along with time, and the average size was approximately 170 nm. Capping of Z. zerumbet extract on the surface of gold nanoparticles was confirmed by Fourier transform infrared spectroscopy (FTIR). In general, phenolic compounds or flavonoid compounds were considered to be the reducing agent. However, zerumbone was identified as the reducing agent in this study. The resulting oxidized products were characterized by high-performance liquid chromatography-mass spectrometry (HPLC-MS). As a result, the solvent was proven to be involved in nanoparticle synthesis. Overall, Z zerumbet@Au NPs showed great potential to be used in cosmetic- or biomedicine-related fields.